CORPORATE GOVERNANCE DAN MANAJEMEN LABA PADA BEBERAPA PENELITIAN SKRIPSI PERGURUAN TINGGI, STUDI META ANALISIS - Angeline, Angeline; Meiden, Carmel (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2018)
Topic about corporate governance effect on earnings management has been researched by many researcher and still exist until now. The existing research provides both consistent and inconsistent results with different levels of significance. This study aims to integrate thesis results of higher Education related to the topic of corporate governance effect on earnings management in Indonesia period 2004-2014. Data collection method use observation method with as the output thesis. The sample of this research is 23 thesis student of higher education. The sampling technique is purposive sampling technique. Researcher use meta analysis technique to integrate the result of the thesis research and show conclusions related to the effect of corporate governance on earnings management. The result of this research shows that managerial ownership, institutional ownership, the size of the board directors and the size of board commissioners effect earnings management. The correlation of the weak independent variable to the dependent variable is shown by the average correlation value below 0.25. In addition, this study also proves that the validity of agency theory in several manufacturing companies, banking, LQ45 in the study period 2004 - 2014.